Tecnologias de Informação e Comunicação em Bibliotecas Escolares: em busca de um espaço dinâmico - Lanzi, Lucirene Andréa Catini [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio; Ferneda, Edberto [UNESP] (My University, 2014)
The Information and Communication Technologies (ICT) can be combined with the acquisition of academic knowledge and cultural development of students, as they improve their information literacy, and why not say, also digital. Weaim in this research seek references and present experiences that encourage a new concept of school library with the use of ICT in teaching and learning in individual and collective development of the student community. To complement this study we prioritized the following objectives: to insert the technology into the routine of a school library; identify the informational and technological profile of adolescents; understand the needs and technological resources they use to obtain information in daily life and also analyze the importance the effective participation of the school library in the educational context of the school, through greater interaction between the librarian, teacher and pedagogical coordination seeking a cooperative and informal ICT teaching and learning for along with the students, sharing the search for information and knowledge, in a conscious and responsible way. Chosen as theoretical foundation the cognitive studies of Jean Piaget, witch explains how the stages of assimilation and accommodation of knowledge in cooperative practices work. As a methodology was developed a participatory-action research, to learn the behavioral state of young people and adolescents, based on the model of information search for the everyday life (Everyday Life Information Seeking) – ELIS, developed by Finnish researcher Savoleinen (2006), as well as identify the informational and technological profile of adolescents from two selected approaches in the scientific literature (HUGUES-HASSEL; AGOSTO, 2007; UCL, 2008). Thus, came up the initiative to create a Confraternity of the Library in a collaborative digital environment, providing the participants discussion and learning technologies as well as digital information literacy enhancement.

As Tecnologias de Informação e Comunicação (TIC) podem ser aliadas na aquisição do conhecimento acadêmico e cultural dos estudantes, na medida em que aperfeiçoam sua competência informacional, e por que não dizer, também digital. Objetivamos nesta pesquisa buscar referências e apresentar experiências que favoreçam um novo conceito de biblioteca escolar com a utilização das TIC no processo de ensino aprendizagem e no desenvolvimento individual e coletivo da comunidade estudantil. Como complemento desse estudo priorizamos como objetivos específicos: inserir as tecnologias na rotina de uma biblioteca escolar; identificar o perfil tecnológico e informacional dos adolescentes; compreender as necessidades e os recursos tecnológicos por eles utilizados, para obter informação no cotidiano e, ainda analisar a importância da participação efetiva da biblioteca escolar no contexto educacional da escola, por meio de maior interação entre o bibliotecário, o professor e a coordenação pedagógica, buscando um ensino aprendizagem cooperativo e informal das TIC, para juntamente com os alunos, compartilharem a busca de informações e conhecimento, de forma consciente e competente. Escolhemos como embasamento teórico os estudos cognitivos de Jean Piaget, que esclarece como funcionam as etapas de assimilação e acomodação do conhecimento por práticas cooperativas. Como metodologia, foi desenvolvida uma pesquisa-ação-participativa, para conhecer o estado comportamental dos jovens e adolescentes, baseada no modelo de busca de informação para o cotidiano (Everyday Life Information Seeking) – ELIS, desenvolvido pelo pesquisador finlandês Savolainen (2006), como também identificar o perfil tecnológico e informacional dos adolescentes a partir de duas abordagens selecionadas na literatura científica (HUGUES-HASSEL; AGOSTO, 2007; UCL, 2008). Assim, surgiu a iniciativa de se criar uma Confraria da Biblioteca, para, num ambiente digital colaborativo, proporcionar aos participantes discussão e aprendizado de tecnologias, bem como aprimoramento da competência informacional digital.
Information and communication technologies in school libraries: in search of a dynamic area